Investigating Epstein-Barr Virus IgG Antibodies as a Biomarker for Oncogenesis and Immune Evasion in Lung Cancer among Iraqi Patients - Abbass, Ruqaya K.; Rasoul, Lubna M. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Lung cancer is the predominant cause of cancer-related mortality globally, accounting for 18.4% of all cancer fatalities, leading to significant economic loss and societal hardship. EBV was identified in 1964 as the premiere human oncogenic virus; it currently contributes to over 200,000 cancer cases annually and around 1.8% of all cancer-related deaths globally. The KRAS gene belongs to the family of rat sarcoma viral oncogenes (RAS), it was identified in lung cancer located on the short arm of chromosome 12 (12p11.1–12p12.1) in 1982.Objectives:  The study aims to analyze the complex molecular interactions among Epstein-Barr virus (EBV) IgG seropositivity, KRAS mutation-induced immunogenicity, and the genetic polymorphism rs121913238, emphasizing their combined effects on driving oncogenic signaling pathways, evading immune surveillance, and altering the tumor microenvironment to promote lung cancer initiation, progression, and phenotypic diversity. Methods: A total number of 100 serum and whole blood samples were collected.  Immunological assay procedure (ELISA) was conducted to measure the concentration of Anti-EBV IgG followed by two steps of molecular analysis: conventional PCR and gene polymorphism by Sanger sequencing technique to detect the targeted SNP in 30 samplesResults:  The results indicated that EBV IgG levels were markedly higher in patients than in controls (P = 0.0003). The data indicate a possible role of EBV in lung cancer, necessitating additional investigation into its contribution to disease etiology.The targeted SNP was not detected in either of the samples in the selected region, another SNP (rs11836509) was detected in 8 samples (6 patients and 2 controls). Conclusion: The viral infection showed no significant relation to the KRAS mutation, but it has a relation with the disease, the (rs11836509) correlates with lung carcinoma.